2019
DOI: 10.1002/dmrr.3114
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines and macrophage markers during pregnancy—Possible role for sCD163 in prediction and progression of gestational diabetes mellitus

Abstract: Aims The risk of gestational diabetes mellitus (GDM) is increased in overweight and obese women potentially involving secreted mediators from adipose tissue. Our main aim was to evaluate if circulating adipokines and monocyte/macrophage markers were dysregulated in GDM and the influence body mass and indices of glucose metabolism had on this association. We further explored if early detection of these markers improved prediction of GDM and if they remained modified during long‐term follow‐up. Materials and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 43 publications
(80 reference statements)
0
19
0
Order By: Relevance
“…To date, most studies of chemerin and GDM have been cross-sectional, with limited data from prospective studies. 7 9 25 One study among native Scandinavians reported higher levels of chemerin at four time points throughout pregnancy (14–38 GWs) among women who developed GDM, 7 although differences were not statistically significant. The relatively small number of GDM cases (n=48) in the previous study may have impeded their ability to detect statistical differences in chemerin levels, which were observed in our study with a larger number of GDM cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, most studies of chemerin and GDM have been cross-sectional, with limited data from prospective studies. 7 9 25 One study among native Scandinavians reported higher levels of chemerin at four time points throughout pregnancy (14–38 GWs) among women who developed GDM, 7 although differences were not statistically significant. The relatively small number of GDM cases (n=48) in the previous study may have impeded their ability to detect statistical differences in chemerin levels, which were observed in our study with a larger number of GDM cases.…”
Section: Discussionmentioning
confidence: 99%
“… 8–15 Only one study was conducted among a diverse population, however, it included a small number of women with GDM (n=48). 7 …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found increased concentrations of leptin and upregulation of TNF-α signalling genes, as well as upregulated IL-1 receptor and IL-8 receptor genes in GDM placentas compared to NGT placentas (Radaelli et al 2003, Lappas et al 2005a, Enquobahrie et al 2009, Magee et al 2014. In addition, GDM pregnancies exhibit increased serum macrophagic marker sCD163 in early pregnancy (Ueland et al 2019), and increased placental expression of macrophagic markers CD14+ and CD68+ at term, accompanied by enhanced mRNA expression of TNF-α and IL-6 (Yu et al 2013, Mrizak et al 2014. Importantly, these pro-inflammatory cytokines are known to promote the expression and secretion of the chemokines IL-8 and MCP-1 in the placenta (Lappas et al 2004(Lappas et al , 2006.…”
Section: Inflammationmentioning
confidence: 99%
“…We have previously measured adipokines, monocyte/macrophage and inflammatory markers in this cohort (22). As seen in Table 4, leptin, resistin, chemerin, sCD163, sCD14, CRP were positively correlated with CETP activity during pregnancy.…”
Section: Cetp Activity In Gdm and Women Who Develop Prediabetesmentioning
confidence: 82%
“…During LPS/TLR4 interaction sCD14 is released from monocytes/macrophages and notably, LPS from gut microbiota could interact with monocytes/macrophages outside the intestine through gut leakage mechanisms into the systemic circulation, which could be particular relevant during pregnancy (32). We recently demonstrated enhanced sCD163 in early GDM pregnancies with an inverse association with β-cell function, particularly in women with high BMI (22).…”
Section: Discussionmentioning
confidence: 99%